Motivation schemes, career development and job satisfaction of the business process outsourcing industries in Iloilo City - Adolfo, Abegail; Estremadura, Frolan; Laraño, Joseph Eduard III; Pangue, Melissa; Tinducan, Marian Lou
Business Processing Outsourcing firms have been sprouting in Iloilo City. A large percentage of fresh graduates who are unemployed have been very much interested in pursuing a career in the call center industry. This study is focused in the motivation schemes, career development and level of job satisfaction of business process outsourcing industries in Iloilo City. Specifically it identified that the primary motivation schemes of call centers are based on monetary values. Motivation in call centers is highly regarded because much of its work force are composed of highly competed individuals who work at a time of the day when in fact everyone must be sleeping. Call centers also offer training and development in English proficiency, communication skills and interpersonal skills improvement. Promotions are done commonly every two years for employees who have done their tasks remarkably. Call center agents are employed contractually, many of which are involved in the business for six months only. This makes call center agents concerned with the tenure of their job. Call centers managers are highly competiitive in motivating their employees and most of them are democratic. Call centers must enrich and develop skills through ongoing work place opportunities. Call centers can build off-phone time into the day offer rotational job assignments, special projects; cross training, increased responsibilities and advancement opportunities that will address call center agents' nurture a yearning for a lifelong personal and professional growth. The study found out that he motivation schemes and career development programs are being offered in the call center industries here in Iloilo City, and majority of the call center agents are already satisfied with their present job. However, those who are dissatisfied cited the need for more work space to work comfortably since the common setting of call centers require the agents to sit in a shared desk. Some are even conscious with the ergonomics of the workplace, that is, to change the physical lay-outs of the office and even the colors of the paint on the walls. Furthermore, it was found out that despite the fact call center agents are already satisfied with their present job the majority of them are willing to give them up once presented with better work opportunities that allows them to practice their skills and competencies in their intended professions.